IMPACT OF CURRENTLY ADOPTED NUTRITIONAL TRENDS ON SUDANESE HEALTH - Mohamed Bulla, Haghamad Allzain (International Journal of Research -GRANTHAALAYAH, 2020)
Food items reflect the culture and tradition of any nation and respond to national and global demographic, social and economic changes. Sudanese as old African nation has rich and distinct nutritional heritage represent the traditional Sudanese diets which able to serve the nutritional requirement of linear growth of body and the brain for centuries. The present century has witnessed unprecedented globalization in term of mobilization of individuals and commodities with dramatic cultural changes. As direct result of such events, as elsewhere, western style of energy dense refined food items replaced the centuries’ long traditional nutrients and fibers dense diets. The aim of this article is to evaluate effects of shifting from traditional diets to the modern adopted food items on Sudanese health, as there are increasing discrepancy of neonatal physical parameters and rising incidence of obesity and non-communicable diseases. The study concluded that increasing urbanization and shifting from the traditional diets has grave consequences on human health in Sudan, with increasing incidence of low birth weight, obesity, diabetes, and hypertension as detail in the main text of this article.